Protein metabolism and related body function: mechanistic approaches and health consequences - Tomé, Daniel; Benoit, Simon; Azzout-Marniche, Dalila (Proceedings of the Nutrition Society, 2021)
The development and maintenance of body composition and functions require an adequate protein intake with a continuous supply of amino acids (AA) to tissues. Body pool and AA cellular concentrations are tightly controlled and maintained through AA supply (dietary intake, recycled from proteolysis and de novo synthesis), AA disposal (protein synthesis and other AA-derived molecules) and AA losses (deamination and oxidation). Different molecular regulatory pathways are involved in the control of AA sufficiency including the mechanistic target of rapamycin complex 1, the general control non-derepressible 2/activating transcription factor 4 system or the fibroblast growth factor 21. There is a tight control of protein intake, and human subjects and animals appear capable of detecting and adapting food and protein intake and metabolism in face of foods or diets with different protein contents. A severely protein deficient diet induces lean body mass losses and ingestion of sufficient dietary energy and protein is a prerequisite for body protein synthesis and maintenance of muscle, bone and other lean tissues and functions. Maintaining adequate protein intake with age may help preserve muscle mass and strength but there is an ongoing debate as to the optimal protein intake in older adults. The protein synthesis response to protein intake can also be enhanced by prior completion of resistance exercise but this effect could be somewhat reduced in older compared to young individuals and gain in muscle mass and function due to exercise require regular training over an extended period.